SEKENEM DAN SEKEPAT Perlindungan terhadap Perempuan dalam Tradisi Budaya Masyarakat Terpencil di Kabupaten Lombok Tengah, Nusa Tenggara Barat - Munawirsazali Munawirsazali (Sabda: Jurnal Kajian Kebudayaan, 2019)
This paper discusses about the concept of protecting women in the cultural tradition of isolated communities in Lombok Tengah. The results of research in this paper is that the sociocultural system of these isolated communities in Lombok Tengah uphold the dignity of local women. The protection of women in these isolated communities in Lombok Tengah has been done through what were locally called ‘sekenem’ and ‘sekepat’ as a place for a girl to receive her visitor. Each house is required to have ‘sekenem’ or ‘sekepat’ as a place for their daughter to receive her guest or friend. The system of the culture of isolated communities in Lombok Tengah can provide for the women morally and socially protected.